New methods of reconstruction of foundry production units - О. I. Ponomarenko; V. V. Torjanik (Литьë и металлургия)
In the article there is offered the method of development and reconstruction of casting houses and their subsystems, based on using of the procedure of system analysis, theory of reliability, hierarchical structure of graph theory, probabalistic automatons, mathematical and simulation technique. For the first time in foundry production practice there is offered such mathematical model, which allowed to link the reliability parameters of equipping functioning with the usable technology, to create the optimal structures of casting houses subsystems.